Intense and broad photoluminescence at room temperature in structurally disordered Ba[Zr0.25Ti0.75]O-3 powders: An experimental/theoretical correlation - Cavalcante, L. S.; Anicete-Santos, M.; Sczancoski, J. C. [UNESP]; Simoes, L. G. P. [UNESP]; Santos, M. R. M. C.; Varela, José Arana [UNESP]; Pizani, P. S.; Longo, Elson [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Intense and broad photoluminescence (PL) emission at room temperature was observed on structurally disordered Ba[Zr0.25Ti0.75]O-3 (BZT) powders synthesized by the polymeric precursor method. BZT powders were annealed at 573 K for different times and at 973 K for 2 h in oxygen atmosphere. The single-phase cubic perovskite structure of the powder annealed at 973 K for 2 It was identified by X-ray diffraction and Fourier transform Raman techniques. PL emission increased with the increase of annealing time, which reached its maximum value in the powder annealed at 573 K for 192 h. First principles quantum mechanical calculations based on density functional theory (B3LYP level) were employed to study the electronic structure of ordered and disordered models. The theoretical calculations and experimental measurements of Ultraviolet-visible absorption spectroscopy indicate that the presence of intermediary energy levels in the band gap is favorable for the intense and broad PL emission at room temperature in disordered BZT powders. The PL behavior is probably due the existence of a charge gradient on the disordered structure, denoted by means of a charge transfer process from [TiO5]-[ZrO6] or [TiO6]-[ZrO5] clusters to [TiO6]-[ZrO6] clusters. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: non-crystalline materials; optical materials; chemical synthesis; ab initio calculations; luminescence